Temporal analysis of apple scab in 'Royal Gala' and 'Fuji' under conventional and organic production systems Análise temporal da sarna da macieira nas cultivares Royal Gala e Fuji sob os sistemas convencional e orgânico de produção - Cesa L.P.* (2006)
Apple scab disease, caused by Venturia inaequalis, is one of the most important threats to apple production. Due to great concern about the risks of environmental contamination and human poisoning, organic production is seen as an alternative, while preserving product quality at the standard of the conventional system. Aiming to evaluate apple scab epidemiology under conventional and organic production systems , a temporal analysis in 'Royal Gala' and 'Fuji' was used, in the edafo-climatic conditions of the Southern Brazil. The incidence was quantified weekly, generating 16 maps in each system of production. Biweekly, the severity of the disease was evaluated in 100 leaves, distributed in four branches, in accordance with the diagramatic scale of Croxall et al (1952) with 12 repetitions. With the data, curves of disease progress were made and the epidemics compared in relation to: a) the beginning of symptom appearance (BSA); b) the time to reach the maximum disease intensity (TRMDI); c) the maximum value of disease severity (ymax); and d) area under the disease progress curve (AUDPC). The incidence data were analyzed by linear regression and adjusted for three empirical models: Logistic, Monomolecular and Gompertz. The cultivars evaluated were susceptible to V. inaequalis, significant differences being detected between cultivars and between production systems. Disease intensity and disease progress rate (r) were higher in the organic than in the conventional system of production. The Logistic epidemiological model was the most appropriate one to describe the disease progress curve.